Western Iceland 1:50,000 - United States. Army Map Service. (Army Map Service, 1941)
Set includes various issues of some sheets and may be used in conjunction with sheets of Iceland 1:50,000, G.S.G.S. 4138. Advance edition"" sheets without series title and number. Relief shown by contours and spot heights. Six classes of roads or trails, two types of internal boundaries and various types of landforms are shown. Modified and revised from Danish maps dated 1910. Includes ""Glossary." Marginal diagram: Index to adjoining sheets. Some sheets include glossary and meters/feet conversion table. Indexed." Scale 1:50,000.